PENGARUH KOMPETENSI, PENGALAMAN KERJA, DAN GENDER TERHADAP KINERJA AUDITOR (STUDI EMPIRIS PADA KAP DI KOTA MALANG) - Gustamin Abjan; Maslichah Maslichah; Junaidi Junaidi (Universitas Islam Malang, 2021)
This study is aimed to determine the effect of the competence, work experience and gender on the auditor performance of public accounting firm in the Malang city. Source of data using primary data and using purposive sampling method share to 84 questionnaire, but we only get back 60 respondents and data that can be processed are 44. The result of this study indicate that the variable competence and work experience have a positive effects on the auditor performance. While, the variable gender does not effect on the auditor performance of public accounting firm in the Malang city. Keywords : auditor performance, competence, work experience, gender.